A cross sectional study on the prevalence of reproductive tract infections amongst married women in the rural area of Surendranagar district - Thekdi, Komal P.; Patel, K. G.; Patel, Nita K.; Thekdi, Pukur I. (International Journal of Research in Medical Sciences, 2017)
Background: In the recent years, the issue of gynaecological problems of poor women in the developing countries has been receiving increasing attention. High levels of gynaecological morbidity, especially reproductive tract infections and sexually transmitted infections may turn out to be fatal if not treated properly. Objectives of current study were to find out the prevalence of reproductive tract infections amongst married women, to co-relate the disease with certain socio demographic variables and to assess the awareness about reproductive tract infections in the study population. Methods: Sample size - Various community based studies carried out in the different regions world showed the prevalence of reproductive tract infections 36-84%. The sample size of study as per statistical calculation (4pq/l2, where p =50, q=100-p and l= 10% of p) came out to be 400. Method of Sampling - Prior enlisting all villages of Surendranagar district, one village was selected randomly. After random selection the village found was Khodu. Results: 56.5% of women reported either one or more symptoms of reproductive tract infections; vaginal discharge (29.7%) was the commonest symptom. Basic awareness about disease was 64.0%; Maximum prevalence of reproductive tract infections (62.90%) was found in the age group of 25-34 years. Conclusions: There is a significant association between socio-economic class, educational status and women having symptoms of reproductive tract infections.